2021
DOI: 10.1080/20008198.2021.1890937
|View full text |Cite
|
Sign up to set email alerts
|

PTSD and complex PTSD in adolescence: discriminating factors in a population-based cross-sectional study

Abstract: Background: Chronic and repeated trauma are well-established risk factors for complex posttraumatic stress disorder (CPTSD) in adult samples. Less is known about how trauma history and other factors contribute to the development of CPTSD in adolescence. Objective: The aim of this study was to assess the potential contribution of trauma history and social factors to CPTSD in adolescents. Method: In a cross-sectional community study of 1299 adolescents aged 12-16 years, PTSD (n = 97) and CPTSD (n = 108) was asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 32 publications
(37 reference statements)
4
41
1
Order By: Relevance
“…Japan is an Asian country with a collectivistic culture and a technologically developed population with a complex history and high exposure to natural disasters. We included social factors, such as social support, loneliness, financial difficulties in family along with trauma exposure in the study to explore factors associated with PTSD/CPTSD in adolescence based on previous empirical evidence (Daniunaite et al ., 2021) as relevant to the cultural contexts in both countries in our study.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Japan is an Asian country with a collectivistic culture and a technologically developed population with a complex history and high exposure to natural disasters. We included social factors, such as social support, loneliness, financial difficulties in family along with trauma exposure in the study to explore factors associated with PTSD/CPTSD in adolescence based on previous empirical evidence (Daniunaite et al ., 2021) as relevant to the cultural contexts in both countries in our study.…”
Section: Introductionmentioning
confidence: 89%
“…This study is part of the larger multicultural longitudinal study Stress and Resilience in Adolescence (STAR-A) initiated at the Center for Psychotraumatology at Vilnius University in Lithuania (Kazlauskas et al ., 2020; Zelviene et al ., 2020; Daniunaite et al ., 2021). The relevant Institutional Review Boards approved the study in both Japan and Lithuania.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…17 These estimates are relatively higher than other general-population studies among adults 18,19,20 and thus, establishing prevalence rates across different populations of young people is necessary. There is a dearth of research investigating factors which increase a young person's susceptibility to CPTSD however, interpersonal trauma, 6,7,17,21 cumulative trauma, 7,19,22 female gender 7,23 and social factors 17 have been indicated as particularly salient risk factors. Different patterns of comorbidity have also been observed in young people compared with adult populations, 21,24 however such research is limited.…”
Section: Limitationsmentioning
confidence: 99%
“…Likewise, Yaşar et al ( 2021 ) observed that the fear of COVID-19 was effective on trust in colleagues. In their study investigating the potential effects of the COVID-19 pandemic on generalized trust, Thoresen et al ( 2021 ) associated pandemic-related concerns and high perceived health threat levels with lower levels of generalized trust. This result obtained this study suggested that different anxieties and fears in the pandemic process affected the stress levels of professionals, and as perceived stress increased, trust in relationships decreased.…”
Section: Discussionmentioning
confidence: 99%